Intellectual Capital and Firm Value in Indonesian Insurance Companies: The Role of Profitability Mediation and Underwriting Risk Moderation - Khu Sumiati; Taufiq Hidayat; Sparta Sparta (Politeknik Siber Cerdika Internasional, 2026)
Background: The Indonesian insurance industry faces increasing pressure to leverage intellectual capital (IC) for competitive advantage, yet evidence on its impact on profitability and firm value remains limited and inconsistent. Objective: This study examines the effect of intellectual capital, measured by the Adjusted Value-Added Intellectual Coefficient (A-VAIC), on the firm value of insurance companies in Indonesia, and investigates the role of profitability as a mediating variable and underwriting risk as a moderating variable. Methods: Using a quantitative approach, panel data from 14 Indonesian insurance companies listed on the Indonesia Stock Exchange over 2019–2024 were analyzed (84 firm-year observations) employing Seemingly Unrelated Regression (SUR), Moderated Regression Analysis (MRA), and Sobel test. Results: The results indicate that intellectual capital has no significant effect on profitability (β = −0.000509; p = 0.696) but has a significant negative effect on firm value (β = −0.155; p = 0.027). Profitability (ROA) has no significant effect on firm value (PBV) (β = −16.02; p = 0.062). Underwriting risk (loss ratio) significantly weakens the IC–profitability relationship (β = −0.000146; p = 0.003), while profitability does not mediate the IC–firm value relationship (Sobel z = 0.392; p = 0.695). These findings suggest that IC effectiveness is contingent on underwriting risk management and that IC information is not yet fully interpreted by the market. Practically, insurance firms should prioritize underwriting efficiency and transparent IC disclosure to enhance market valuation. Conclusion: The findings show that intellectual capital has a significant negative effect on firm value, while profitability does not mediate this relationship. Underwriting risk weakens the effect of intellectual capital on profitability, indicating that its value is not yet fully recognized by the market.